Constraining Fault Damage Zone Properties From Geodesy: A Case Study Near the 2019 Ridgecrest Earthquake Sequence. Issue 5 (28th February 2023) - Xu, Xiaohua; Liu, Dunyu; Lavier, Luc
Abstract: Seismologic studies have reported seismic velocities reduction and V p / V s ratio changes over damage zones associated with seismogenic faults. The structure and elastic properties of these damage zones indicate the maturity of faults and affect the rupture dynamics of future seismic events. Therefore, they contain critical information about fault properties that could inform seismic hazards. Here we present a geodetic modeling approach to constrain velocity changes and elastic properties of fault damage zones under stress perturbation from nearby earthquakes. Compared to seismic tomographic analysis that is usually limited by resolution, this geodetic approach provides tighter constraints on the elastic properties and geometry of the damage zone at shallow depths. Our results imply that a major component of the shallow strain release is distributed and inelastic. The existence of numerous shallow faults either may indicate a locally detached shallow layer or they are remnants from earlier fault evolution. Plain Language Summary: Ruptures of large earthquakes tend to fracture the materials nearby, thus creating a zone with lower seismic velocity, which is known as fault damage zone. Understanding the structure and mechanics of this zone will help reveal the status of fault evolution and seismogenic depth for future ruptures. To achieve that, we developed a geodetic modeling approach to determine the geometric and physical parameters of fault damage zones, utilizing observations from high‐resolution Interferometric Synthetic Aperture Radar and strain release estimates from kinematic fault slip models. By searching the parameters in a specific order, each unknown could be uniquely constrained from the observed deformation profiles. The approach works well with fault damage zones under compliant motion induced by the stress from nearby earthquakes. The method is straightforward, computationally efficient and is applicable even to a fault damage zone with 250 m width near the 2019 Ridgecrest earthquake sequence. Our study suggests that these structures are quite shallow and accommodate a major component of shallow strain release. Key Points: We developed a geodetic modeling approach to constrain structural and mechanical properties of fault damage zones The approach is straightforward, computationally efficient, and works well even over a small fault damage zone with 250 m width The existence of many shallow fractures indicates distributed shallow strain release over transtensional shear zones